2005
DOI: 10.1021/jo051545k
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Systematic Underestimation of Reaction Energies by the B3LYP Model as the Number of C−C Bonds Increases: Why Organic Chemists Should Use Multiple DFT Models for Calculations Involving Polycarbon Hydrocarbons

Abstract: [reaction: see text] Computational studies of three different reaction types involving hydrocarbons (homolytic C-C bond breaking of alkanes, progressive insertions of triplet methylene into C-H bonds of ethane, and [2+2] cyclizations of methyl-substituted alkenes to form polymethylcyclobutanes) show that the B3LYP model consistently underestimates the reaction energy, even when extremely large basis sets are employed. The error is systematic and cumulative, such that the reaction energies of reactions involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
180
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(199 citation statements)
references
References 40 publications
12
180
0
6
Order By: Relevance
“…The M062X functional appears to offer comparable isomerization energy prediction performance to the best performing currently available dispersion corrected functionals against this benchmark dataset.The performance of various levels of quantum chemical methods for estimating the isomerization energies (∆ isom E) and enthalpies (∆ isom H) of organic compounds has been the focus of a number of investigations over the past several years [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. This attention is primarily driven by the poor performance of many popular density functionals -most notably the B3LYP functional -with regard to these types of intramolecular rearrangements.…”
mentioning
confidence: 99%
“…The M062X functional appears to offer comparable isomerization energy prediction performance to the best performing currently available dispersion corrected functionals against this benchmark dataset.The performance of various levels of quantum chemical methods for estimating the isomerization energies (∆ isom E) and enthalpies (∆ isom H) of organic compounds has been the focus of a number of investigations over the past several years [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. This attention is primarily driven by the poor performance of many popular density functionals -most notably the B3LYP functional -with regard to these types of intramolecular rearrangements.…”
mentioning
confidence: 99%
“…We investigated density functional theories with theory of van der Waals densities for modeling exchange-correlation senergies for the nanotubes [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . The double ζ-basis set including polarize orbitals was used for boron and nitrogens atoms while single ζ-basis setincluding polarize orbital was applied for the TWCNTs, respectively 53 .…”
Section: Computational Detailsmentioning
confidence: 99%
“…For non-covalent interactions,the BLYP methods are unable for describing van der Waals [51][52][53] TWCNTs systems by medium-ranges interaction such as interaction between three tubes of TWCNTs. The B3LYP and some other functional are not suitable for illustrating the exchanges and correlations energies indistant medium-range non-bonded system obviously.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of ability of B3LYP and most other popular functional to correctly describe medium-range of exchange and correlation energy limits their applicability for distant non-bonded systems of two electrodes and dielectric thickness in a capacitor. Moreover, some recent studies have shown that inaccuracy for the medium-range exchange energies lead to large systematic errors in the prediction of molecular properties 136 . A monolayer of graphene was optimized and allowed to relax to its minimum energy structure.…”
Section: Computational Detailsmentioning
confidence: 99%